PENGEMBANGAN SMART EDIBLE PACKAGING BERBAHAN KITOSAN DAN GLISEROL DENGAN PENAMBAHAN EKSTRAK BUNGA TELANG DAN TEPUNG CANGKANG TELUR AYAM - Tjahjadi, Gregorius Richardo Ghevyn; Yoshari, Rachel Meiliawati; Utomo, Adrianus Rulianto; Jati, Ignasius Radix AP (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2024)
Food packaging is often made of materials that do not decompose, which is not environmentally friendly. To address this issue, eco-friendly packaging options is needed, such as smart edible packaging. This study aims to develop chitosan based edible film with butterfly pea extract and eggshell powder as active agents and investigate its characteristics. This study used a two-factor factorial design, which involved adding butterfly pea flower extract in ratios of 0:1, 1:250, and 1:125, as well as eggshell flour in concentrations of 0%, 0.15%, and 0.3%. ANOVA (α=5%) and DMRT test (α=5%) were used to analyze the data and determine any significant differences between treatments. The results showed that the interaction between butterfly pea flower extract and eggshell flour had an effect on the tensile strength values, which ranged from 1.2170-11.4710 N/mm2, percent elongation of 20.875-62.62%, and WVTR of 47.9857-201.3018 g/ m2/24 hours/day. Butterfly flower extract had a significant impact on total anthocyanins of 0.0512-0.2560 mg Eqv. Cyanidin-3-glucoside/100 g sample, total phenol of 275.9375-1106.6232 mg GAE/100 g sample, and antioxidant activity of 3.2062-87.4859 %RSA. Smart edible packaging can also change color from blue to green, which indicates changes in the quality of chicken meat during storage.